Collaborative Governance of Tourism Development in Sidomulyo Village, Jember Regency - Nurdiansyah, Dino Alfian; Wicaksono, Itok (Journal of Geosciences and Environmental Studies, 2024)
This research aims to determine the collaborative governance of tourism development in Sidomulyo Village. Then, in this study, qualitative research was used with a descriptive method, and data gathering procedures included observation, interviews, and recording, as well as primary and secondary data sources. The theory employed is Emerson and Tina Nabatchi's. The findings of this study show that collaborative governance can influence the dynamics of collaboration, cooperative activities, and the impacts of village tourism development. It can be concluded that collaborative governance of tourism development in Sidomulyo Village has a social and economic impact, even if the growth is not maximized due to various impediments.